Analysis of Serbian Primary Antiphospholipid Syndrome Patients Confirmed a Strong Association Between Livedo Reticularis and Arterial Thrombosis: A National Cross-Sectional Cohort Study. Issue 7 (12th October 2022) - Djokovic, Aleksandra; Stojanovich, Ljudmila; Stanisavljevic, Natasa; Matic, Predrag; Colic, Danijela; Skrijelj, Daniel; Djokic, Sandra; Filipovic, Branka
Abstract : Background: Antiphospholipid syndrome (APS) is characterized by antiphospholipid antibodies (aPLs) associated with thrombosis (arterial and/or venous) and/or obstetrical manifestations. However, various manifestations, which are considered to be noncriteria manifestations, are frequently found in APS. Aim: The purpose of this study was to evaluate whether noncriteria manifestations may be found more frequently in subjects with thrombotic and/or obstetrical APS ("criteria" manifestations) in a population of patients with primary APS (PAPS). This study presents the results from our national cohort. Patients and Methods: This is a cross-sectional study of 360 PAPS patients. Data regarding the presence of thrombocytopenia, livedo reticularis, chorea, and valvulopathy were analyzed. The aPL analysis included the detection of anticardiolipin antibodies (aCLs: immunoglobulin G [IgG]/IgM), anti-β2 glycoprotein I (IgG/IgM), and lupus anticoagulant positivity. Results: In our cohort, livedo reticularis was significantly related to arterial thromboses in the same way as valvular manifestations (valvular vegetations and valvular thickening and dysfunction not related to age) ( p = 0.0001, p = 0.013, respectively). Age was strongly related to all the noncriteria manifestations analyzed. Thrombocytopenia was significantly related to β2 glycoprotein I IgG and lupus anticoagulant positivity ( p = 0.043, p = 0.030, respectively), as well as to double and triple aPL positivity ( p = 0.041, p = 0.013 respectively). Moreover, in a multivariate model, livedo reticularis was strongly and independently related to arterial thrombosis in our cohort (odds ratio, 2.010; confidence interval, 1.229–3.288; p = 0.005). Conclusion: This cross-sectional analysis of a large cohort of Serbian PAPS patients confirmed a strong relationship between livedo reticularis and arterial thrombosis, suggesting a more cautious approach regarding the presence of noncriteria manifestations, especially livedo reticularis, in APS.